Menganalisis Mata Pelajaran Ilmu Pengetahuan Alam Di Kelas IV Madrasah Ibtidaiyah Muhammadiyah Pulau Tengah Kecamatan Tambang Kabupaten Kampar - Rosdah, Rosdah (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
The purpose of this study was to analyze learning materials about ecosystems and life processes in natural science subjects in class IV Madrasah Ibtidaiyah Muhammadiyah Tengah Island, Tambang District, Kampar Regency. Ecosystems in the world are divided into two, namely natural ecosystems and artificial ecosystems. Natural ecosystems consist of aquatic ecosystems and terrestrial ecosystems. Water ecosystems themselves consist of freshwater ecosystems and saltwater ecosystems and terrestrial ecosystems consist of forest, grassland, desert, tundra and taiga ecosystems. Artificial ecosystems are ecosystems created by humans to meet human needs. Every living thing that exists on this earth certainly experiences the process of life. The process of life occurs in humans, animals, plants and all living things that exist in nature. In the process of life, creatures in nature certainly need many things, such as the need to sustain life in nature. Humans, plants and animals are living things. Humans breathe, plants grow tall, animals move